Assessment of Balance Recovery Strategies during Manipulation of Somatosensory, Vision, and Vestibular System in Healthy and Blind Women - Mansour Sahebozamani; Asma Salari; Abdolhamid Daneshjoo; Fatemeh Karimi Afshar (Shiraz University of Medical Sciences, 2019)
Background: Individuals with vision loss are at an increased risk of falls. Understanding what factors contribute to postural instability within this population is a necessary step towards the development of training programs and rehabilitation targeted at reduction of falls in this population. The aim of this study was to assess the balance recovery during manipulation of somatosensory, vision, and vestibular system in healthy and blind persons. Methods: This causal-comparative study, thirty healthy (28.18±0.47 years) and blind (29.22±0.24 years) subjects were selected as samples. Balance recovery strategies in various situations were recorded by six high-speed cameras after sudden movement of a treadmill. Independent T-test test was used for data analysis. Results: The results of this study indicated that the mean of hip and ankle swings in different conditions was significantly higher in the blind group than in the healthy group, both in the anterior-posterior and posterior-anterior disturbances. There was also a significant difference between the ratio of hip/ ankle ROM (the dominant strategy for balance recovery) in all situations (P<0.05). Conclusion: The findings of this study revealed that both healthy and blind groups had different mechanisms and responses for balance recovery after anterior-posterior and posterior-anterior perturbation (the dominant strategy investigated in each position separately). Also, the results showed that blind individuals more resort to hip strategies to maintain their postural stability and prefer to rely on somatosensory information to restore balance as the dominant sensory system.